Treatment of chest pain - Ismawi, Hidayatul Radziah (2023)
Three classes of drugs, used either alone or in combination, are effective in treating patients with angina. These drugs lower the oxygen demand of the heart by affecting the blood pressure, venous return (how much blood is return to the heart), heart rate and contractility.